Yhteistyön kääntöpuoli - kun itseorganisoituminen epäonnistuu ja ilmaantuminen yllättää - Jalonen, Harri; Lindell, Juha; Puustinen, Alisa; Raisio, Harri (Hallinnon tutkimus, 2013)
The hidden side of co-operation: When self-organisation fails and emergence overtakes As a practice, co-operation is seen in an affirmative light. It is identified with the progress and improvement of the state of affairs without much questioning. Apart from the potential benefits of co-operation this paper claims that with co-operation comes something unintended and unexpected that should be examined closely. Like Janus, co-operation has two faces. In addition to improving the means of providing public services, co-operation introduces new political, ethical, economic, and cultural dilemmas. Using the complexity lens, this exploratory paper focuses on dilemmas introduced by the "bottom-up organising" of co-operation - particularly on self-organisation processes, which produce emergent patterns that no-one chooses or wants. The objective of the paper is to theoretically explore the meaning of self-organisation and emergence in complex co-operation settings and to seek potential new theoretical frames to address the phenomenon.